Evaluation in the Trap of Error: Identifying Common Evaluation Errors in the Context of E-Learning - Mahmoodi, Maryam; Shams, Gholamreza; Khorasani, Abasalt; Safai Movahed, Saeed (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to identify evaluation errors in e-learning environments. The research adopted a qualitative approach using the meta-synthesis method. The research population consisted of scholarly articles published in international databases including Scopus, ERIC, and ScienceDirect, which were retrieved based on predefined keywords within the time frame of 2010 to 2025. In this study, various parameters such as title, abstract, content, and methodological quality were considered. Accordingly, 969 articles related to the research topic were initially evaluated, and ultimately, 20 articles were purposively selected. Data analysis was conducted using the seven-step meta-synthesis method proposed by Sandelowski and Barroso (2007). The results of the meta-synthesis led to the identification of nine categories of e-learning evaluation errors, including: (1) ethical errors, (2) design errors, (3) implementation errors, (4) feedback errors, (5) measurement errors, (6) contextual errors, (7) technological errors, (8) human errors, and (9) security errors. These findings indicate that improving the quality of evaluation in e-learning environments requires careful attention to multiple dimensions of error and a thorough reconsideration of evaluation design and implementation processes.